2011
DOI: 10.1007/s10228-011-0224-4
|View full text |Cite
|
Sign up to set email alerts
|

The annual cycle of spermatogenesis in Lipophrys pholis (Blenniidae), a recently proposed sentinel species for pollution monitoring

Abstract: Since reproductive parameters are common endpoints in pollution monitoring, the description of the spermatogenesis of Lipophrys pholis, a recently proposed sentinel species, is of critical importance. Mature males were used to determine the annual maturation cycle, using a stereological approach. The spermatogenic cycle was classified into three stages: early spermatogenesis (May), mid spermatogenesis (September), and spawning (November and January). The testes were asynchronously arranged with various cell ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 30 publications
5
9
0
Order By: Relevance
“…Similar results were observed for males capable of multiple spawning episodes. Such results also agree with previous studies on the species (Ferreira et al., , ). Furthermore, the sex ratio of L. pholis observed here was most likely 1:1 throughout the year.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Similar results were observed for males capable of multiple spawning episodes. Such results also agree with previous studies on the species (Ferreira et al., , ). Furthermore, the sex ratio of L. pholis observed here was most likely 1:1 throughout the year.…”
Section: Discussionsupporting
confidence: 94%
“…Histological observations showed that almost all stages of gonadal sexual development were present simultaneously in the ovaries and testes throughout the year. The observed five main stages of maturity corresponded to the existing literature for this species (Ferreira et al., , ; Ismail et al., 1990; Qasim, ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Interestingly, GSI also produced fairly good results for L. pholis males (Ferreira et al 2011). The stereological approach, although highlighting several similarities between sites and sampling seasons (e.g.…”
Section: Discussionmentioning
confidence: 99%